2011
DOI: 10.1371/journal.pone.0026658
|View full text |Cite
|
Sign up to set email alerts
|

Human Evolution and Osteoporosis-Related Spinal Fractures

Abstract: The field of evolutionary medicine examines the possibility that some diseases are the result of trade-offs made in human evolution. Spinal fractures are the most common osteoporosis-related fracture in humans, but are not observed in apes, even in cases of severe osteopenia. In humans, the development of osteoporosis is influenced by peak bone mass and strength in early adulthood as well as age-related bone loss. Here, we examine the structural differences in the vertebral bodies (the portion of the vertebra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 50 publications
1
44
0
2
Order By: Relevance
“…Comparative studies characterizing the microarchitecture of trabecular bone have consistently found that humans have a lower bone volume fraction (BV/TV) than chimpanzees. Whether in the humeral head (Shaw and Ryan, 2012;Scherf et al, 2013), first metacarpal head (Lazenby et al, 2011), thoracic vertebra (Cotter et al, 2011), femoral head (Shaw and Ryan, 2012), calcaneal body (Maga et al, 2006), talar body (DeSilva and Devlin, 2012), or medial metatarsal heads (Griffin et al, 2010), humans consistently possess lower BV/TV than chimpanzees. Under the Achilles tendon insertion, however, we found a trend towards slightly higher BV/TV in humans than in chimpanzees, though this trend was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies characterizing the microarchitecture of trabecular bone have consistently found that humans have a lower bone volume fraction (BV/TV) than chimpanzees. Whether in the humeral head (Shaw and Ryan, 2012;Scherf et al, 2013), first metacarpal head (Lazenby et al, 2011), thoracic vertebra (Cotter et al, 2011), femoral head (Shaw and Ryan, 2012), calcaneal body (Maga et al, 2006), talar body (DeSilva and Devlin, 2012), or medial metatarsal heads (Griffin et al, 2010), humans consistently possess lower BV/TV than chimpanzees. Under the Achilles tendon insertion, however, we found a trend towards slightly higher BV/TV in humans than in chimpanzees, though this trend was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of this relative gracility remains uncertain, and this uncertainty hinders the development of strategies for mitigating fracture risk and morbidity. The progressive gracilization of the Homo postcranial skeleton was originally detected in cortical bone structure (1, 2), but has now been demonstrated in the trabecular bone microstructure of joints (12,14,(16)(17)(18)(19), where osteoporotic fracture risk is highest (20). Most notably, in an analysis of thoracic vertebral bodies, Cotter et al (12) found that young adult humans have significantly lower trabecular bone volume fraction (BV/TV) and thinner vertebral shells than similarly sized apes.…”
mentioning
confidence: 99%
“…trabecular bone | gracilization | human evolution | biomechanics | mobility C ompared with other hominoids and extinct hominin species, more recent humans possess relatively gracile postcranial skeletons (1)(2)(3)(4)(5)(6)(7)(8)(9). One of the consequences of this gracility in contemporary humans is an increased fracture risk associated with age-related bone loss and osteoporosis [hip fractures alone are projected to reach 6.26 million per year globally by 2050 (10)] (11)(12)(13)(14)(15). The etiology of this relative gracility remains uncertain, and this uncertainty hinders the development of strategies for mitigating fracture risk and morbidity.…”
mentioning
confidence: 99%
See 2 more Smart Citations